Convenience Beats Trust: The Reality of Cryptocurrency Consumer Choices - Fomin, Vladislav; Kerulis, Ugnius; Grāmatiņš, Rihards; Gürpinar, Tan (Information & Media, 2025)
Background: Despite the financial technology (Fintech) industry being marked as a strategic development direction in many countries, cryptocurrency products show low adoption rates. Purpose: This study investigated factors affecting consumer trust in cryptocurrency products, particularly exchanges and crypto wallets. Methods: A three-stage multi-method approach was adopted: two non-probability convenience surveys and a systematic literature review. The initial survey (N=45) was followed by literature review (N=16) and a follow-up survey (N=95). Qualitative and quantitative analysis techniques were used. Findings: Trust must be understood as a versatile concept, with consumers perceiving different factors differently when choosing cryptocurrency products. Two key findings emerged: convenience, rather than trust, is the biggest factor attributed to cryptocurrency product popularity and adoption. Second, an inverse relationship exists between trustworthiness and popularity of information sources about cryptocurrency products, with less popular sources being more trusted. Consumers rely on convenience-based attributes like the ease of use and accessibility, which indirectly influence trust perception. Conclusions: Trust degree is not bound to specific products or services but depends on consumer intentions and knowledge, among other factors. Research implications: The authors suggest policy and innovation development directions to increase consumer trust in cryptocurrency products.
Keywords: crypto-currency; crypto wallet; crypto exchange; consumer trust; consumer preferences; consumer knowledge